THE EFFECTIVENESS OF PUBLIC SERVICE DIGITALIZATION IN CORRUPTION PREVENTION FOR GOOD GOVERNANCE IN INDONESIA - Fery Muchtar Ashari; Rob van Gestel (SYNTIFIC, 2026)
Background. The digital transformation of public administration has become a central strategy for governments seeking to improve service delivery, enhance transparency, and strengthen accountability. In Indonesia, digitalization initiatives such as electronic government systems, online licensing platforms, digital procurement, electronic taxation, and integrated public service applications have been promoted as instruments for improving governance and reducing opportunities for corruption. While digital technologies have the potential to minimize direct interactions between citizens and public officials, thereby reducing discretionary decision-making and rent-seeking behavior, questions remain regarding their actual effectiveness in preventing corruption. This study aimed to analyze the effectiveness of public service digitalization as an anti-corruption mechanism from a legal and governance perspective. Research Methods. This study uses a normative juridical approach to analyze Indonesian legislative frameworks pertaining to public administration, electronic government, anti-corruption laws, and digital public services. It also incorporates international and comparative viewpoints. Findings. Digitalization contributes significantly to corruption prevention through enhanced transparency, traceability, accountability, and procedural standardization. However, challenges remain regarding institutional capacity, digital inequality, cybersecurity risks, regulatory fragmentation, and the persistence of corruption in digitally mediated environments. Conclusion. Digitalization should not be viewed as a purely technological solution but as part of a broader legal and institutional reform agenda aimed at strengthening integrity, public accountability, and good governance.